Kajian Ekonomi Penambangan Batubara di PT. Indomining, Sanga-Sanga, Kutai Kartanegara, Kalimantan Timur pada Desain Penambangan Tahun 2018-2027 - Sovi Mailadiniya; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Based on the coal price index issued by the global coal new castle index, coal prices experienced an increase in mid-2016, as of 2017 coal prices reached $80-100 per ton. To obtain profits, companies need to increase production targets by re-planning mining designs. Before changing the mining design, the total production target for overburden stripping was 87,077,536 bcm and coal production was 6,022.83.3. After a change in mining design, the production target increased, the total overburden production target was 212,815.00 bcm and the coal production target was 13,390.00 tons. In the re-planning of the mining design, it is necessary to assess economic feasibility by considering the need for excavators and transport equipment, production targets, and costs to be incurred during mining.In carrying out this research, the author combines theory with field data, so that both approaches are obtained from problem solving. The research method used in this th esis is a quantitative research method. This research is more directed to descriptive research, which is one type of research that aims to solve problems by collecting data, compiling, analyzing and interpreting it. Based on production targets and results of productivity studies, overburden stripping uses 8 units of Caterpillar 390D excavators and 36 units of Caterpillar 773E OHT. Coal mining uses 1 units of Hitachi ZX 470 excavators and      6 hino FM 260Ti dumptruck units. The total costs incurred during mining amounted to $966,405,923.28 and the total profits obtained were $81,178,110.72. The feasibility of the investment plan after the change in mining design obtained a positive NPV, IRR value of 43% and a payback period of 3,49 years. Keywords: Production Target, Equipment Needs, Costs, Benefits, NPV, IRR, Payback Period